PENERAPAN METODE PEMBELAJARAN SIMULASI DENGAN TEKNIK SOSIODRAMA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU MATERI KEGIATAN POKOK PADA SISWA KELAS VII MTS AL-HIDAYAH SEMESTER GANJIL - Lusi Endang Sri Darmawati (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
This study aims to increase students 'learning activities from very low to very high as well as students' understanding until they reach the KKM set in an integrated social studies subject. This research is a Classroom Action Research (CAR) which is carried out in 2 cycles which include planning, action and observation, and reflection. Determination of the research location using the purposive area method, namely in class VII-A MTs Al Hidayah. Collecting data in this study using the method of observation, tests, interviews and documents. The data analysis used is descriptive analysis with a qualitative approach. The results showed that the application of the simulation method with the sociodrama technique could increase the activity and understanding of class VII-A students which was realized by the daily test scores in accordance with the KKM of Integrated Social Studies subjects at MTs. Al Hidayah. This is evidenced from the results of the implementation of cycle I and cycle II. The results of observations regarding activity showed an increase in all activity indicators which initially entered the medium criteria, after the implementation of the action in cycle II increased to reach very high criteria. The increase in student understanding in accordance with the KKM can be seen from the increase in the average score of students' daily tests which initially was 73.38 with good criteria in cycle I, increasing to 84.91 with very good criteria in cycle II. These results have fulfilled the completeness individually, namely> 70. Classical completeness also increased, which initially was 83.87% in cycle I, increasing to 90.55% after the implementation of cycle II. The number of students in cycle II had fulfilled classical completeness, namely> 85%.